NEUROLOGICAL AND NEUROIMAGING FACTORS ASSOCIATED WITH POST-STROKE FATIGUE OVER THE SECOND HALF YEAR AFTER ACUTE CEREBROVASCULAR EVENTS - Delva, I.I. (World of Medicine and Biology, 2018)
Post-stroke fatigue (PSF) is a common syndrome for stroke survivors. The study was aimed to identify clinical and neuroimaging factors associated with different PSF domains over the second half year after acute cerebrovascular events (ACE). There were examined 194 patients at 6, 9 and 12 months after ACE. Global PSF and PSF domains were measured by multidimensional fatigue inventory-20 scale. It had been identified the significant prevalence of global PSF and physical PSF in stroke patients in comparison with TIA. In univariate logistic regression analysis, in stroke patients it had been found reliable associations between MRS score and risk of global PSF as well as risk of PSF domains related to physical activity. Infratentorial infarcts were significantly associated with increased risk of global PSF and white matter lesion extension, according to Fazekas scale score, was directly associated with significant higher risk of mental and motivational PSF. Decreased post-stroke functional ability, infratentorial ischemic stroke location and leukoaraiosis grade could be prognostic factors for certain PSF domains over the second half year after ACE.